A new species of Pristimantis (Anura: Strabomantidae) from Andean cloud forests of northern Peru - Chaparro, Juan C.; Motta, Ana P.; Gutiérrez, Roberto C.; Padial, José M. (Zootaxa, 2012)
We describe a new species of Pristimantis from cloud forests of the eastern versant of the Andes in northern Peru. Thetype locality lies in Quebrada del Vino, Provincia San Ignacio, Departamento Cajamarca, Peru. The new species is mostsimilar to P. crucifer, P. eriphus, P. flavobracatus, P. leucorrhinus, P. lucasi, and P. vilcabambae, with which it shares thepresence of large conical eyelid tubercles, ulnar tubercles, and heel and tarsal tubercles as well as flash colours on the groinsurrounded by bold black stripes and white stripes. The new species can nonetheless be distinguished from all of them by,having tympanic membrane and annulus, by males having nuptial pads and vocal slits, and by having finger discs scarcely enlarged and truncated with ungual flap not indented.